2012
DOI: 10.1002/cne.23116
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐capture microdissection and transcriptional profiling of the dorsomedial nucleus of the hypothalamus

Abstract: Identifying neuronal molecular markers with restricted patterns of expression is a crucial step in dissecting the numerous pathways and functions of the brain. While the dorsomedial nucleus of the hypothalamus (DMH) has been implicated in a host of physiological processes, current functional studies have been limited by the lack of molecular markers specific for DMH. Identification of such markers would facilitate the development of mouse models with DMH-specific genetic manipulations. Here we used a combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 99 publications
(124 reference statements)
1
26
0
Order By: Relevance
“…This is consistent with our previous finding that NPW mRNA is not detected in the adult DMH (Tanaka et al, 2003). Furthermore, this observation is supported by results from microarray analysis using RNA from adult mouse DMH in which no expression of NPW was detected (Draper et al, 2010;Lee et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…This is consistent with our previous finding that NPW mRNA is not detected in the adult DMH (Tanaka et al, 2003). Furthermore, this observation is supported by results from microarray analysis using RNA from adult mouse DMH in which no expression of NPW was detected (Draper et al, 2010;Lee et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Yoshida et al [68] observed that SCN neurons innervate the HCRT field medial to the fornix. The multiplicity of regional inputs to the HCRT field and heterogeneity of LH/DMH cell populations [71], [72] and activation patterns [73], [74] suggest that both direct and indirect SCN inputs may regulate Per1 expression in this region.…”
Section: Discussionmentioning
confidence: 99%
“…Slides were then dehydrated in a graded ethanol series followed by 5 minutes in xylenes. The Arcturus Veritas Microdissection System (Molecular Devices) was used to isolate each nucleus based on defined neuroanatomical boundaries 30 as described previously 31 . Nuclei collected are listed in Supplementary Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…Due to sufficiently high expression, it was not necessary to pre-amplify 18S rRNA, which was used as the normalizer gene. All gene expression levels were measured with an Applied Biosystems 7900HT Sequence Detection System using the efficiency-corrected ΔCt method as previously described 31,32 . The anatomic specificity of the LCM dissections was confirmed by QPCR for the expression of known marker genes in each nucleus.…”
Section: Methodsmentioning
confidence: 99%